Comparing volunteer policing in Malaysia, England and Wales and the United States of America: cross-national findings. Issue 1 (5th January 2021) - Cheah, Phaik Kin; Britton, Iain; Callender, Matthew; Wolf, Ross; Knight, Laura; Unnithan, N. Prabha
Abstract : Purpose: This article offers a tri-national comparison between Malaysia, England and Wales and the United States of America Design/methodology/approach: It is based on reviewing, collating, comparing and contrasting previous research findings and official reports on the topic with a view to identify recurrent commonalities in the three countries studied. Findings: Three key common themes are identified and presented in the article: (1) The relevance of the cultural positioning of volunteers in policing; (2) the importance of understanding the roles and capability of police volunteers; (3) recognizing prerequisites for recruitment of volunteers and the nature of their subsequent training. Research limitations/implications: We suggest that more detailed comparative studies of volunteer policing structures and officer roles would be valuable. Practical implications: The practice implications of these findings are discussed, and the potential value of and major challenges in carrying out cross-national national comparative study in the field of volunteer policing shown. Social implications: The paper discusses important issues in the role and value of police volunteerism to criminal justice and society. Originality/value: There are few international comparisons of volunteer policing and even fewer that compare approaches between Western and Eastern countries. This is the first study to do so.